THE CONCEPT OF ILLICIT DRUG TRAFFICKING AND PSYCHOTROPIC SUBSTANCES - MUSAEV, Djamaliddin (Journal of Fundamental Studies, 2024)
The fight against drug addiction is given top priority both ideologically and in legislative and law enforcement practice. However, constant changes in legislation and regulations, as well as in judicial and investigative practice, are often not as effective as expected. Analysis of the results of this activity shows that a number of these changes are aimed not at strengthening the fight against drug crime, but at weakening it, and creates preferences for the most dangerous drug criminals.